THE PARTNERSHIP OF GOVERNMENT AND CREATIVE INDUSTRY IN DEVELOPING CREATIVE TOURISM IN KAMPUNG BATIK KAUMAN, SURAKARTA - Restu, Aulia; Endah Trihayuningtyas; R. Wisnu Rahtomo (International Journal of Sustainable Competitiveness on Tourism, 2022)
The development of creative tourism that relies on the creative industry in Kampung Batik Kauman requires cooperation and partnership with tourism stakeholders so that the planning and implementation go according to the goals of sustainable tourism. This study aims to identify the actual conditions of creative tourism and identify the form of partnership that exists between the government and the creative industry in Kampung Batik Kauman. The method used in this study is a descriptive method with a qualitative approach. The participants of this study were the government of Surakarta City and the creative industry involved in creative tourism activities and involved in cooperation or partnerships in Kampung Batik Kauman. The results of this study indicate that creative tourism in Kampung Batik Kauman meets the criteria for developing creative tourism. The form of partnership that exists between the government and the creative industry in developing creative tourism is a complementary partnership, where the benefits have been felt by the government and the creative industry but are still limited.